miR-107 modulates chondrocyte proliferation, apoptosis, and extracellular matrix synthesis by targeting PTEN - Tian, Feng (Int J Clin Exp Pathol, 2019)
Background: Osteoarthritis (OA) is a common chronic degenerative disease, and the chondrocyte is reported to be a key player in OA progression. Increasing evidence has verified the regulatory role of miRNAs in OA. However, the function and underlying mechanism of miR-107 in cartilage function are still not clarified. Methods: Abundance of miR-107 and PTEN mRNA were detected by qRT-PCR. Relative protein levels of PTEN, Bcl-2, Bax, Caspase-3, aggrecan, collagen II, MMP-13, and MMP-9 were measured by western blotting (WB). A biological web server Targetscan was used to predict the putative binding sites between miR-107 and PTEN, and luciferase reporter assay was employed to further verify the true interplay between them. Cell proliferative or apoptotic activity was assessed by MTT or flow cytometry (FCM) analysis. Results: miR-107 was downregulated and PTEN was upregulated in OA tissues. PTEN could be negatively regulated by miR-107 by targeted interaction. Interference of PTEN induced proliferation of C28/I2 cells, but inhibited cell apoptosis. Restoration of PTEN reversed miR-107-stimulated cell proliferation and miR-107-inhibited apoptosis in C28/I2 cells. Furthermore, enforced abundance of miR-107 promoted the expressions of aggrecan and collagen II protein, while it attenuated MMP-13 and MMP-9 expression in C28/I2 cells, which was overturned by PTEN restoration. Conclusion: miR-107 induced chondrocyte growth and ameliorated cartilage degradation by targeting to PTEN, providing a potential therapeutic target for OA.